ÐŸÐ°Ð¼â€™ÑÑ‚Ñ– ÐšÐ°Ñ‚ÐºÐ¾Ð²Ð° Ð†Ð³Ð¾Ñ€Ñ Ð†Ð²Ð°Ð½Ð¾Ð²Ð¸Ñ‡Ð° - Problems of Cryobiology and Cryomedicine, Editorial Board (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(4): 370